Herpes simplex virus type 1 ICP8: helix-destabilizing properties. - Boehmer, P E (1993)
The major single-stranded DNA-binding protein, ICP8, of herpes simplex virus type 1 (HSV-1) is one of seven virus-encoded polypeptides required for HSV-1 DNA replication. To investigate the role of ICP8 in viral DNA replication, we have examined the interaction of ICP8 with partial DNA duplexes and found that it can displace oligonucleotides annealed to single-stranded M13 DNA. In addition, ICP8 can melt small fragments of fully duplex DNA. Unlike a DNA helicase, ICP8-promoted strand displacement is ATP and Mg2+ independent and exhibits no directionality. It requires saturating amounts of ICP8 and is both efficient and highly cooperative. These properties make ICP8 suitable for a role in DNA replication in which ICP8 destabilizes duplex DNA during origin unwinding and replication fork movement.